Transplantation of olfactory ensheathing cells decreases local and serological monocyte chemoattractant protein 1 level during the acute phase of rat spinal cord injury. Issue 17 (17th October 2022) - Wang, Yiqun; Gong, Minjie; He, Xijing; Wu, Yutong; Li, Yuhuan; Li, Jialiang; Wen, Zhijing; Wang, Yibin; Gu, Pengzhen; Li, Haopeng
Abstract : Objectives: Monocyte chemoattractant protein 1 (MCP1) is one of the most upregulated cytokines in the spinal cord and serum throughout acute spinal cord injury (SCI). Olfactory ensheathing cells (OECs) transplantation improves SCI through multiple mechanisms, including immunomodulation. Our study aimed to investigate whether OECs ameliorate acute inflammation after SCI by modulating MCP1 expression. Methods: We established a standardized clinically relevant contusion model using the NYU impactor. OECs were administered to the injured spinal cord via microinjection 30 minutes after injury. Rat locomotor functions were assessed by the Basso–Beattie–Bresnahan scale score. Time-course histopathological (H&E and IHC) analyses were performed to record rapid changes in acute inflammation at lesion epicenters. Serum MCP1 level was detected by ELISA assay. Results: BBB scores showed improved locomotor functional recoveries in the OECs transplantation group after SCI ( P < 0.05). Staining of H&E and CD68 illustrated that OECs transplantation attenuated inflammatory response by reducing lesion areas and infiltrating myeloid cell numbers. We further revealed significantly decreased MCP1 levels in the spinal cord and serum after OECs transplantation ( P < 0.05). Noteworthily, distinct expression levels of MCP1 were found in rats undergoing a mild injury (cord impacted from a 10-mm height) compared to the moderate injury (25-mm) group. Conclusion: Our study reports that transplantation of OECs promotes locomotor functional recovery after SCI and alleviates acute inflammation by decreasing local and serological MCP1 levels. We provide preliminary evidence that MCP1 might serve as a potential biomarker to reflect the severity of SCI, which is of great interest in future studies.